Diagnosis of hypertonicity of the masticatory muscles at a dental appointment - Yu. A. Makedonova; A. A. Vorobev; A. N. Osuko; A. V. Alexandrov; D. Yu. Dyachenko; A. G. Pavlova-Adamovich (Эндодонтия Today)
Summary. The purpose of the study. Hypertonus of the masticatory muscles is a fairly common pathology that leads to the development of parafunctional masticatory activity. At the same time, the nature of the course of the pathology becomes long-lasting, leading to irreversible consequences. Patients often do not pay attention to minor pain in the area of the masticatory muscles, so hypertonus of the masticatory muscles is diagnosed randomly. In view of the variety of clinical symptoms from headaches to the phenomena of oral stomalgia, the diagnosis of hypertension is extremely difficult. Also, there is currently no single algorithm for the management of such patients.Materials and methods. In the presented scientific study, a survey of 189 patients who applied to a dental clinic for the treatment of dental caries and its complications, a professional examination was conducted. All patients were examined according to the method of diagnosis of muscle hypertonus developed by us. The methodology includes a thorough collection of anamnesis, questionnaires (PSM-25, VAS, MAS, author's methods), the use of objective research methods, including: OPTG, CT, ultrasound, the author's method of determining the degree of mouth opening.Results. Muscle hypertonus of varying severity was diagnosed in 80% of cases, high stress level on the PSM-25 scale in 71% (135), the presence of morning pain in the area of the masticatory muscles in 55%(104). An assessment of muscle tone on the MAS scale confirmed a significant increase in masticatory muscle hypertonicity in 34% of cases. These additional methods of investigation confirmed the presence of hypertonicity of the masticatory muscles in patients with an objective clinical picture. In the study of this area, the main role is played by the clinician, only if all the diagnostically valuable information is available, it is possible to formulate an optimal treatment plan and avoid aggravation of the patient's condition due to incorrect diagnosis and treatment.Conclusions. The application of the developed diagnostic method contributes to the random detection of parafunctional activity of the masticatory muscles at a dental appointment, as well as to the final diagnosis of masticatory muscle hypertonus.